Stress-constrained shell-lattice infill structural optimisation for additive manufacturing - Huangchao Yu; Jiaqi Huang; Bin Zou; Wen Shao; Jikai Liu (Virtual and Physical Prototyping, 2020)
This paper presents a numerical study on stress-constrained shell-lattice infill structural optimisation. This problem is inherently challenging for several reasons: (i) different stress measures have to be used for the solid shell and the porous lattice infill, and the two types of stress constraints make the problem extremely complex to solve and (ii) involvement of the shell layer further complicates the optimisation problem modelling and its solution. To address these challenges, two stress constraints were formulated, i.e. a von Mises stress-based constraint for the solid shell layer and a Tsai-Hill yield criteria-based constraint for the porous lattice. Then, level set function is adopted to represent the shape of the shell layer and the constant-thickness shell layer is modelled based on the signed distance feature. Then, a comprehensive and accurate sensitivity result is derived to guide the concurrent structural shape and lattice density optimisation. A few numerical examples will be studied to prove the effectiveness of the developed algorithm. Some interesting phenomena have been observed, such as the soft narrow band at the shell-lattice interface to mitigate stress concentration.